The Effect of XP-endo Finisher R and PIPS Technique Using Er: YAG Laser on Removal of Gutta-percha in Root Canals Obturated with Two Different Obturation Techniques - Ali Erdemir; Gülşen Ermiş; Dilek Hançerlioğulları; Ali Türkyılmaz; Gözde Akbal Dinçer (Selcuk Dental Journal)
Background: The aim of this study is to compare the efficacy of XP-endo finisher R file and PIPS technique using Er: YAG laser on removal of gutta-percha in root canals obturated with two different obturation techniques. Methods: The root canals of sixty single-rooted teeth were prepared with ProTaper Next Rotary instruments up to X3 (Dentsply, Ballaigues, Switzerland). Half of the root canals were obturated with cold lateral condensation technique and the other half with System B technique (Kerr Corporation, CA, USA) and BioRoot RCS sealer (Setodent, Louisville, USA) was used in all groups as a root canal sealer. After one week, all root canals were retreated using Protaper Universal retreatment instruments (Dentsply, Ballaigues, Switzerland) and enlarged to ProTaper Next X5 File at the working length. Both groups were divided into 3 subgroups according to the additional cleaning methods: control group without an additional cleaning method, XP-endo Finisher R or PIPS technique using Er: YAG laser. Finally, all teeth were split longitudinally and images were taken using an operation microscope (Carl Zeiss, Heidelberg, Germany). The images were analyzed by Image J program. Two-way ANOVA and Tukey tests were used for statistical analysis. Results: There was a statistically signiﬁcant difference between the canal filling techniques applied in the evaluation of remnants (p=0.010). There was no significant difference between additional cleaning methods (p=0.196). Conclusion: Within the limitations of this study, cleanliness is more difficult in root canals obturated with System B technique. Use of additional cleaning method was not effective in removal of root canal filling materials.